Pulmonary epithelial-myoepithelial carcinoma without AKT1, HRAS or PIK3CA mutations: a case report - Naoki Yanagawa; Ayaka Sato; Masao Nishiya; Masamichi Suzuki; Ryo Sugimoto; Mitsumasa Osakabe; Noriyuki Uesugi; Hajime Saito; Tamotsu Sugai (BMC, 2020)
Abstract Background Pulmonary epithelial-myoepithelial carcinoma is a rare subtype of lung cancer. Because of its rarity, the molecular information on this carcinoma is insufficient. Case presentation We report a case of pulmonary epithelial-myoepithelial carcinoma without AKT1, HRAS or PIK3CA mutations in a 76-year-old woman. Computed tomography revealed a tumor located in the left lower lung. Thoracoscopic left lower lobectomy was performed. Histopathologically, the tumor consisted of duct-like structures and polygonal and spindle cell features. The duct-like structures were composed of two distinct cell layers. The inner layer consisted of cuboidal cells that were positive for pan-cytokeratin and negative for p63, whereas the outer layer consisted of polygonal and spindle cells that were positive for p63 and weakly positive for pan-cytokeratin. We evaluated mutations in AKT1, BRAF, CTNNB1, HRAS, KRAS and PIK3CA but did not detect any mutations. Conclusion Pulmonary epithelial-myoepithelial carcinoma is a rare subtype of lung cancer, with only 56 previous cases reported in the English literature. The genetic alterations in pulmonary epithelial-myoepithelial carcinoma are still unknown. We examined the 6 genes mutation analysis, however no mutation was detected.